The issue of artistic idea in poetry of Artay, the famous poet of Inner Mongolia - . Togtomzh (Nomadic Civilization: Historical Research, 2023)
A poem is a bright pearl on a literary gem. Even if you write poetry in your native language, you should have a sacred and clear glory that you should receive the love and gratitude of your readers. After writing poems for several decades, he not only advanced the development of his native language, but also enriched the literary treasury of the Mongolian nation, and was a distinguished artist and outstanding contribution to the literary work. After Saitsogt, he was recognized as the representative of the Mongolian poets of the second generation. When we read poetry, we enjoy multifaceted pleasures, such as imagery, symbolism, ineffable thinking, melody, and meaning. It is the joy and happiness that only poets can give to others with meaningful and melodious language. In the eyes of others, the rain was a dark cloud, but in the eyes of D. Nyamsuren, the rain was “white...”. Also O. Mr. Dashbalbar said to someone that “Poets are people who are the voice of their people who think on a Mongolian and global scale, and are a symbol of their nation”. Analysis of his poems proves that Artai is a national poet.